The Morphology of Inner Cell Mass Is the Strongest Predictor of Live Birth After a Frozen-Thawed Single Embryo Transfer - Ai, Jihui; Jin, Lei; Zheng, Yu; Yang, Peiwen; Huang, Bo; Dong, Xiyuan (Frontiers in Endocrinology, 2021)
Background The scoring system for human blastocysts is traditionally based on morphology; however, there are controversies on the effect of morphology parameters on pregnancy outcomes. The aim of this study is to evaluate the predicting value of each morphology parameter on pregnancy outcomes in a setting of single embryo transfer. Methods This is a retrospective cohort study on patients undergoing frozen-thawed single blastocyst transfer at our center, between Jan. 2009 and Dec. 2018. A total of 10,482 cycles were analyzed. The blastocysts were scored according to the expansion and hatching status, morphology of inner cell mass (ICM), and cells of trophectoderm (TE). The primary outcome measure was live birth rate. One-way analysis of variance, chi-square test, and multiple logistic regression were used for statistical analysis. Results The clinical pregnancy rate was lower in the blastocysts of stage 3 (48.15%), compared with those of stage 4 (56.15%), stage 5 (54.91%), and stage 6 (53.37%). The live birth rate was lower in the blastocysts of stage 3 (37.07%), compared with those of stage 4 (44.21%) and stage 5 (41.67%). The rates of clinical pregnancy (A: 66.60%, B: 53.25%, C: 39.33%) and live birth (A: 54.62%, B: 41.29%, C: 28.45%) were both decreased with decreasing grade of ICM morphology, and these differences were pairwise significant. The miscarriage rate of blastocysts with ICM grade A was lower, compared with ICM grade C (17.53 vs. 27.66%). Blastocysts with TE morphology of C had lower rates of clinical pregnancy (43.53%) and live birth (32.57%), compared with those with TE morphology of A and B (clinical pregnancy rate: 64.26% for A, 58.11% for B; live birth rate: 52.74% for A, 45.64% for B). There were no significant differences in rates of clinical pregnancy, live birth, and miscarriage between the blastocysts with TE grade A and B. Conclusions The blastocyst expansion stage, ICM grade, and TE grade are all associated with pregnancy outcomes. ICM grade is the strongest predictor of live birth. A blastocyst with stage 4–5, ICM grade A, and TE grade A/B should be given priority for single embryo transfer.